Membangun Strategi Bisnis Berkelanjutan: Analisis SWOT pada Mamam Ayam - Apsari, Nurlaila; Daspar, Daspar (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the internal and external conditions of Mamam Ayam MSMEs using SWOT analysis and the Internal (IFE) and External (EFE) Factor Evaluation matrix. Mamam Ayam is a culinary business with processed chicken with distinctive flavors and interesting menu variations. The method used is a qualitative case study with data collection through interviews, observation, and documentation. The analysis focuses on identifying strengths, weaknesses, opportunities and threats that affect the business. Results show strengths in taste, competitive pricing, and strategic location, while weaknesses are in digital promotion and financial management. Opportunities are open with chicken food trends and delivery services, while threats come from fierce competition and fluctuating raw material prices. These findings form the basis for formulating business development strategies so that Mamam Ayam can improve competitiveness and grow sustainably